PENGEMBANGAN DAN PEMBUATAN MATERI AJAR KOMPONEN ELEKTRONIKA BERBASIS MEDIA PEMBELAJARAN SOFTWARE LECTORA INSPIRE - Candra Hidayat; Putra Jaya (Universitas Negeri Padang, 2020)
This study aims to produce teaching materials for electronic components based on Lectora Inspire software learning media in order to get a decent performance. Creating this media is designed by using the waterfall model software design methods, and it is including: 1) Design, 2) Architecture and Interface Design, 3) Coding/Programming, and 4) Testing. The feasibility test to the results of the development and creating of electronic components teaching material based on Lectora Inspire software was carried out on three main aspects, which consist of the software aspect, the media display design aspect, and the benefit aspect. Based on the results of the feasibility test which was conducted by two media experts. From this, it was obtained the data that, first, the average score of the software aspect was 17, the average score of the media display design aspect was 45.5, and the average score of the benefit aspect was 3. Thus, the average total score was 65.5 of 72. If it refered to the Likert scale table, it showed that the total score which has obtained can be interpreted that the teaching material was categorized as a very decent.